The Role of Professional Organization (PGRI) in Protecting Teachers Right - Heru Novianto; Nurkhasanah; Nurkolis Nurkolis (Lembaran Ilmu Kependidikan, 2025)
The progress of a nation is reflected in its per capita income, life expectancy, and education level. Higher education levels lead to better human resource quality, which is essential for national and global competitiveness. Teachers play a crucial role in the educational process, and their rights must be protected to ensure their effectiveness. This paper examines the role of the Indonesian Teachers' Association (PGRI) in advocating for teachers' rights as outlined in Law No. 14 of 2005. The study employs a qualitative approach, utilizing literature review and case studies to analyze PGRI's efforts in protecting teachers' rights and enhancing their professional development. The findings indicate that PGRI is instrumental in safeguarding teachers' rights, providing legal protection, and promoting their welfare.